BK virus DNA in CSF of immunocompetent and immunocompromised patients. Issue 2 (1st February 2003) - Behzad-Behbahani, A; Klapper, P E; Vallely, P J; Cleator, G M
Abstract : Aim: To investigate the possible aetiological role of BK and JC viruses in immunocompetent and immunocompromised children with suspected encephalitis and meningoencephalitis. Methods: The polymerase chain reaction and microplate hybridisation method was employed for the detection of polyomavirus DNA in 266 CSF specimens collected from immunocompetent and immunocompromised patients. Results: BK virus DNA was detected in three (2.1%) CSF samples taken from patients aged 2–5 years; two were patients with acute lymphocytic leukaemia without overt neurological symptoms, the other was a patient with suspected encephalitis. BK virus DNA was also detected in two (1.6%) CSF samples taken from older children in the age range 10–16 years; both children had suspected encephalitis. JC virus DNA was not found in any CSF sample from either age group. Conclusions: Detection of BK virus in the CSF of immunocompromised and immunocompetent patients with suspected neurological disease suggests that this virus may have had a pathogenic role in the aetiology of this condition.